Pulmonary embolism as a cause of cardiac arrest in a patient after a stroke - Ena Parać; Stjepan Herceg; Marin Boban; Paola Negovetić; Nikolina Borščak Tolić (Liječnički vjesnik, 2023)
Stroke is a medical condition in which the blood supply to the brain is interrupted or reduced. Early in-hospital complications following a stroke are not only pneumonia, increased intracranial pressure and intracerebral bleeding, but also pulmonary embolism (PE). The main cause of PE is venous thromboembolism developed in a paralyzed lower extremity after a stroke.